Potential Use of Recycled Asphalt Pavement (RAP) in Hot MixAsphalt (Journal of Engineering, 2013)
The objective of the present paper is to examine the effect of Recycled Asphalt Pavement (RAP) on marshall properties and indirect tensile strength of HMA through experimental investigation. A mixture with 0% RAP was used as a control mix to evaluate the properties of mixes with 5%, 10%, and 15% RAP. One type of RAP was brought from Bab Al-moadam’s road in Baghdad for this purpose. The experimental testing program included Marshall and Indirect Tensile Strength tests. The results indicated that the bulk density, flow and VFA increase with the increasing of the percentage of RAP, while increasing in RAP results decreases in VTM and VMA values. Furthermore, the stability is changed from 10.1 kN for the control mix to12, 13.6 and 11.7 kN for mixes with 5%, 10% and 15% RAP respectively. The results reveal that the inclusion of RAP into HMA mixtures increases the indirect tensile strength and decreases the values of ITS with the increasing of the test temperature. The results also indicated that increasing the percentage of RAP produces an increasing in temperature susceptibility value. The results of marshall properties and IDT test indicate that the amount of new binder that needs to be added to the RAP mixture can be reduced without significant effects on the quality of the produced mix